Effects of contralateral trunk tilt on shoulder and elbow injury risk and pitching biomechanics in professional baseball pitchers - Escamilla, R. F.; Slowik, J. S.; Fleisig, G. S. (The American Journal of Sports Medicine, 2023)
Background: Baseball pitchers employ various contralateral trunk tilt (CTT) positions when pitching depending on if they have an overhand, three-quarter, or sidearm delivery. There are no known studies that have examined how pitching biomechanics are significantly different in professional pitchers with varying amounts of CTT, which may provide insight into shoulder and elbow injury risk among pitchers with different CTT.